1988
DOI: 10.1063/1.455417
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and microwave investigations of interconversion tunneling in the acetylene dimer

Abstract: A sub-Doppler infrared spectrum of (HCCH)2 has been obtained in the region of the acetylene C–H stretching fundamental using an optothermal molecular-beam color-center laser spectrometer. Microwave spectra were obtained for the ground vibrational state using a pulsed-nozzle Fourier transform microwave spectrometer. In the infrared spectrum, both a parallel and perpendicular band are observed with the parallel band being previously assigned to a T-shaped C2v complex by Prichard, Nandi, and Muenter and the perpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
94
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 133 publications
(102 citation statements)
references
References 49 publications
8
94
0
Order By: Relevance
“…2 This statement is confirmed by more detailed comparisons between observed and simulated structures, as already appearing in Fig. 5-7.…”
supporting
confidence: 67%
See 4 more Smart Citations
“…2 This statement is confirmed by more detailed comparisons between observed and simulated structures, as already appearing in Fig. 5-7.…”
supporting
confidence: 67%
“…1 An extensive experimental and ab initio literature was since devoted to (C 2 H 2 ) 2 , summarized in ref. [2][3][4]. A crucial step in the investigation of this species was the work by Fraser et al 2 These authors demonstrated that 1CH vibrational excitation could occur in either monomeric unit.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations